Materials and applications for sensors and transducers : selected, peer reviewed papers from the 1st International Conference on Materials and Applications for Sensors and Transducers (IC-MAST), May 13-17 2011, Kos Island, Greece - Hristoforou, E.; Vlachos, D. S. (Key engineering materials, 2012)
ICMAST-2011 is an international interdisciplinary conference which covers research and development in the field of materials science; especially those materials which are used for sensors, actuators, and all kinds of transducers. ICMAST-2011 aims to bring together scientists, engineers and product designers in order to fill the gap between research and development. The topics covered by ICMAST-2011 include: new materials development, fabrication technology, sensing principles and mechanisms, actuators, optical devices, electrochemical devices, mass-sensitive devices, gas sensors, biosensors, a.